Organizational Management Of The Arabic Language Course Program At Boarding School Al Hidayah Batu - Al Haqiqy, M. syihabul Ihsan; Aminudin; Destia Harsita; Afifah Anjaina Widodo; Danial Hilmi (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
- As far as talking about organizing, then we talk about organizing that can produce starting from the form, the work system, the structure, the resources, and also other aspects. This study aims to describe the organizational management in the Arabic language course program at Pondok Pesantren Al-Hidayah Batu. This research uses qualitative research methods, case study type. The results of this study are 1) The language course institution at the Al Hidayah Batu Islamic boarding school has standardized organizational management in the current era of globalization, namely flexible organization that is adaptive, responsive, and sensitive to change. 2) for the division of tasks carried out, with the procurement and development of mechanisms to coordinate the duties of each member to become a harmonious and integrated unit, so that organizational members always maintain attention to organizational goals and reduce inefficiency and prevent conflicts that can damage the goals of the vision and mission. the empty gap of this research is renewal in the deepening analysis of global standardized organizing. The implication of this research is that it can provide a reference in the management of organizing Arabic language programs in the world of education.